2022
DOI: 10.1039/d2ra04501j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and behavior of caffeine sorption: affecting factors

Abstract: Caffeine is one of the emerging pollutants with a diverse chemical composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 77 publications
2
16
0
Order By: Relevance
“…The pH PZC provides valuable insights as electrostatic and non-electrostatic interactions between the adsorbate and adsorbent surfaces are important parameters influencing the adsorption efficiency. 34,111 It is observed that the synthesis temperature of the materials has a direct relation with the pH PZC . The higher the synthesis temperature, the greater the value of pH PZC , due to the elimination of some oxygenated functional groups in the structure.…”
Section: Adsorption Studies Of Emerging Contaminantsmentioning
confidence: 99%
See 4 more Smart Citations
“…The pH PZC provides valuable insights as electrostatic and non-electrostatic interactions between the adsorbate and adsorbent surfaces are important parameters influencing the adsorption efficiency. 34,111 It is observed that the synthesis temperature of the materials has a direct relation with the pH PZC . The higher the synthesis temperature, the greater the value of pH PZC , due to the elimination of some oxygenated functional groups in the structure.…”
Section: Adsorption Studies Of Emerging Contaminantsmentioning
confidence: 99%
“…The operational conditions mainly encompass: temperature, sorbate concentration, pH, and solvent nature. 34,111 The synthesized materials were subjected to contact testing with the contaminants PAR, IBU, AMX, EE2, and CAF at 3 and 24 hour intervals under neutral pH conditions (close to 7), as illustrated in Fig. 3A-C.…”
Section: Adsorption Studies Of Emerging Contaminantsmentioning
confidence: 99%
See 3 more Smart Citations